SELEKSI ISOLAT JAMUR DALAM MENGHASILKAN HORMON IAA (Indole Acetic Acid) ASAL TANAH GAMBUT DESA RIMBO PANJANG KABUPATEN KAMPAR - Astriani, Fenny; Fibriarti, Bernadeta Leni; Zul, Delita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Indole Acetic Acid (IAA) is one of group of auxin phytohormones and plays a role to improve plant growth. Beside plants, fungi are also known to be able to produce IAA.This study aimed to select the ability of fungal isolates collection of Microbiology Laboratory, Faculty of Math and Natural Sciences University of Riau in IAA production. Fungal isolates were cultured in medium PDB (Potato Dextrosa Broth)enriched by tryptophan as a precursor of IAA. Indole acetic acid produced by fungi was detected by adding Salkowski reagent and determined quantitatively by the use of colorimetric method. The results showed that 47 fungal isolates were able to produce IAA. The highest IAA production was revealed by isolate RPL4-14 (646,75±0,35 ppm) and the lowest was shown by isolate RPL2-x (4,00±3,53 ppm) when they were culturedin PDB medium enriched by tryptophan. The fungal collection did not only produce IAA in the medium containing tryptophan, but also in the medium without tryptophan as shown by isolate RPL3-10, which has IAA concentration i.e 76,50±0,00 ppm and71,00±0,70 ppm, respectively. Isolates which produced the highest IAA concentration are identified as Penicillium sp.